Comparison Of Reversible Image Watermarking Methods Based On Prediction-Errors - Burhan Baraklı; Emre Altınkaya (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi, 2019)
This study compares two reversible imagewatermarking algorithms applied to a digital image. The first algorithm is amethod based on adaptive watermarking of prediction-errors. With this method,as in the existing reversible image watermarking methods, pixels are embeddedin two different ways according to the values of prediction-errors instead ofapplying the same watermarking algorithm to all pixels in the imageAccordingly,the image pixels are divided into two blocks as uniform and non-uniform. Thewatermarking capacity has been increased by embedding 2-bit to specific pixelsof uniform blocks and 1-bit to specific pixels of non-uniform blocks. Thesecond algorithm is a method based on interpolation errors. In this method,interpolation error is utilized. The two methods compared with each other werecompared with the existing methods in the literature by using computersimulations, and superior and weak aspects of the methods were determined.